Constitution-making in the 21st century - Cheryl Saunders (International Review of Law, 2012)
Constitutions have been made or changed in major ways in more than half the countries of the world in recent decades. This article deals with contemporary approaches to constitution-making, organising the analysis around three key phases: setting the agenda, in terms of both substance and process; design, drafting and approval; and implementation. It argues that, while all constitution-making processes are different, there are some distinctive features of constitution-making in the 21st century that include popular participation, the need to build trust, internationalisation in its various forms and the importance of process. The article canvasses examples of constitution-making practices that have been or are likely to be influential. It identifies and briefly explores some of the key tensions in constitution-making between, for example, international involvement and domestic ownership of a Constitution and public participation and leadership.